2019
DOI: 10.3347/kjp.2019.57.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Downregulates Expressions of 14-3-3β and γ-Isoforms in Mice with Eosinophilic Meningitis Caused by Angiostrongylus cantonensis Infection

Abstract: Steroids are commonly used in patients with eosinophilic meningitis caused by A. cantonensis infections. The mechanism steroids act on eosinophilic meningitis remains unclear. In this mouse experiments, expressions of 14-3-3 isoform β and γ proteins significantly increased in the CSF 2–3 weeks after the infection, but not increasedin the dexamethasone-treated group. Expression of 14-3-3 β, γ, ɛ, and θ isoforms increased in brain meninges over the 3-week period after infection and decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Interestingly, 14-3-3 γ was downregulated after both IP and IT dexamethasone administration. Similarly, in mice, 14-3-3 has been shown to increase in the meninges and CSF of mice with eosinophilic meningitis after infection, and was downregulated upon dexamethasone administration . It has also been found that 14-3-3 γ upregulates glucocorticoid receptor in the liver .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Interestingly, 14-3-3 γ was downregulated after both IP and IT dexamethasone administration. Similarly, in mice, 14-3-3 has been shown to increase in the meninges and CSF of mice with eosinophilic meningitis after infection, and was downregulated upon dexamethasone administration . It has also been found that 14-3-3 γ upregulates glucocorticoid receptor in the liver .…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, in mice, 14-3-3 has been shown to increase in the meninges and CSF of mice with eosinophilic meningitis after infection, and was downregulated upon dexamethasone administration. 48 It has also been found that 14-3-3 γ upregulates glucocorticoid receptor in the liver. 49 Our findings show that treatment with dexamethasone, a glucocorticoid, 14-3-3 levels in the perilymph are downregulated.…”
Section: Discussionmentioning
confidence: 98%
“…An increase in the serum concentration of 14-3-3β in the acute attack group of asthma has been found in comparison with the control group, which indicate that 14-3-3β may participate in the development of acute attack of asthma together and have some value in monitoring the state and prognosis of acute attack of asthma. However, it was that exist no statistical heterogeneity with regard to serum level of 14-3-3β between the chronic persistent group of asthma and the normal control group, which may be associated with the chronic use of ICS-LABA in chronic persistent group of asthma, because one study show that in mice with eosinophilic meningitis dexamethasone can decrease the expression of 14-3-3β protein in the CSF and in brain meninges [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no statistical heterogeneity in the serum level of 14-3-3β between the chronic persistent group and the normal control group, which may be explained by the chronic use of ICS-LABA in the chronic persistent group. In a study of the mouse model of eosinophilic meningitis, dexamethasone was demonstrated to decrease the expression of 14-3-3β protein in the CSF and in brain meninges [ 29 ].…”
Section: Discussionmentioning
confidence: 99%